1977
DOI: 10.1136/bmj.1.6060.551-a
|View full text |Cite
|
Sign up to set email alerts
|

Finger wrinkling as a test of autonomic function.

Abstract: 551Treatment of anticonvulsant osteomalacia with 1 chydroxycholecalciferol Anticonvulsants cause osteomalacia,' possibly by the induction of an altered vitamin-D metabolism in the liver leading to a lack of 25-hydroxycholecalciferol (25-HCC).2 We describe the short-term treatment of a patient with anticonvulsant osteomalacia with small amounts of 1-HCC, a vitarnin-D analogue that has been used in renal osteodystrophy3 and other metabolic bone diseases. Case historyA 5 1-year-old woman with an infantile spastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 2 publications
0
34
0
Order By: Relevance
“…In combination with the mechanical properties of the glabrous finger skin, this reduction in pulp volume results in the typical pattern of ridges and valleys on the tips of fingers and toes [1]. The dependence of finger wrinkling on the autonomic nervous system has led to the use of finger wrinkles as a clinical indicator of autonomic function [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In combination with the mechanical properties of the glabrous finger skin, this reduction in pulp volume results in the typical pattern of ridges and valleys on the tips of fingers and toes [1]. The dependence of finger wrinkling on the autonomic nervous system has led to the use of finger wrinkles as a clinical indicator of autonomic function [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that vasoconstriction and the subsequent loss of volume under the skin is the cause of skin wrinkling (1). Wrinkling of the skin has long been used as a test for sympathetic nerve function (2)(3)(4). However, the mechanism that initiates the vasoconstriction remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the skin wrinkling is used as a test for sympathetic nerve functioning [1,2,3], the trigger of such a test was eluded for a long period of time. In this article, we investigate theoretical possibilities for the cause of skin wrinkling by taking different physical aspects of the phenomenon into consideration.…”
Section: Introductionmentioning
confidence: 99%